EFFECTIVNESS OF DIVORCEMEDIATION IN INDONESIA: COMPARATIVE LEGAL STUDY OF UNITED STATES - Ayu Ningtyas , Dyah Palupi; Al Uyun, Dhia; Susmayanti, Riana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
Victims of Domestic Violence (KDRT) are increasing every year, which is one of the causes of divorce. CATAHU Komnas Perempuan 2022 reported that as many as 4,779 cases of divorce were due to domestic violence. The divorce process is preceded by a mediation stage as a dispute resolution by mediators at the Religious Courts. Mediators who handle divorce cases must be thorough and have a strategy for identifying and dealing with domestic violence. Domestic violence screening (KDRT screening) needs to be done so that the identification of cases of domestic violence can be explained specifically. One of the countries that have implemented screening is the United States, which considers it an appropriate and effective method. Comparison of the legal system becomes an analytical knife regarding the legal process of mediation between Indonesia and the United States. Domestic violence screening conducted in divorce mediation can identify violence that occurs. If there is an act of violence, the mediator can use a different approach during mediation. Mediation should be able to help both parties reach an agreement that is fair and profitable for both while taking into account the rights and obligations of the parties.